Pop-Islam versus Dakwah Ideologis: Strategi Media dan Segmentasi Audiens Habib Husein Ja’far dan Felix Siauw di YouTube - Azharghany, Rojabi; Wahyuniati, Isnani (Institut Agama Islam Syarifuddin Lumajang, 2025)
This study explores a comparative analysis of the digital da’wa strategies of two prominent YouTube figures—Habib Husein Ja’far and Felix Siauw—within the context of the transformation of religious communication in the digital era. Habib Husein Ja’far promotes a moderate and inclusive Pop-Islam approach through collaborations with public figures and the use of popular media formats, while Felix Siauw adopts an ideological da’wa model grounded in sharia and identity politics, without engaging with mainstream celebrities. The study aims to examine their media strategies, audience segmentation, and the impact of their respective narratives on public perception and contemporary da'wah trends. This research employs a qualitative, descriptive-comparative approach using content analysis and virtual ethnography techniques. Data were collected through purposive observation of YouTube video content, audience comments, and media documentation. The analysis is based on Harold Lasswell’s communication theory, mediatization, and personal branding frameworks. The results of the study show the success of a collaborative, adaptive, and contemporary visualization approach in maintaining moderate Islamic discourse in the era of social media algorithms (Habib Husein), as well as the limitations of the expansion of ideological political Islamic narratives that rely on the strength of internal networks without media innovation (Felix Siauw). These findings affirm the premise of mediatization and personal branding that in the digital era, the success of da'wah is determined by the ability to follow the logic and ecosystem of new media, as well as the creation of a persona that is relevant to the trends and needs of its main audience. Keywords: Digital Da'wah; Media Strategy; Youtube